Natural Para Rubber in Road Embankment Stabilization - Salisa Chaiyaput; Nakib Arwaedo; Pitthaya Jamsawang; Jiratchaya Ayawanna (Applied Sciences, 2022)
This is the first study on “ribbed smoked sheets (RSS)” as a geogrid reinforcement in geotechnical engineering. An RSS is a kind of natural para rubber. RSS (grade 3) was designed as a biaxial geogrid with an aperture size of 20 mm × 20 mm and a spacing of 20 mm. The RSS was found to be a significant functional layer when applied to the subbase lateritic soil layer. The lateritic soil with an RSS reinforcing layer was greatly improved regarding the California bearing ratio (CBR). Numerical simulation using two-dimensional finite element software was used to determine the optimal number and positions of the RSS reinforcing layers in road embankment stabilization. The simulation data in terms of horizontal displacement of unreinforced road embankments was validated by the collected data from the actual construction site. The RSS reinforced layer was varied from one to three layers under 61 analysis conditions. The highest safety factor was obtained with two layers of RSS at 0.1H below the top of the road embankment and 0.4H below the first RSS layer, suggesting a suitable installation of the RSS reinforcing layer. The RSS is thus strongly recommended as a reinforcing material in low CBR lateritic soil for the road embankment.
Keywords: Geotechnical Engineering and Soil Stabilization; Geotechnical and construction materials studies; Geotechnical Engineering and Soil Mechanics